Random spot urine protein/creatinine ratio: a reliable method for monitoring lupus nephritis? - Guedes Marques, Maria (Clin Kidney J, 2013)
BACKGROUND: Lupus nephritis (LN) is a common and severe manifestation of systemic lupus erythematosus (SLE) that can lead to end-stage renal disease. According to the Kidney Disease Outcomes Global Improving clinical Guidelines for Glomerulonephritis, spot urine protein/creatinine (P/C) ratio should be used for monitoring LN. However, some reports write that the random spot urine P/C ratio is unreliable in monitoring proteinuria in SLE glomerulonephritis patients. The aim of this study was to evaluate the agreement of these two assay methods. METHODS: The prospective observational study was performed. Fifty-three paired (total 106) spot and 24-h urine collections were evaluated. Statistical analysis: SPSS 20.0. RESULTS: Paired samples t-test did not reveal significant differences between the two-paired assay methods (spot P/C ratio versus 24-h proteinuria and 24-h P/C ratio) and a statistically significant correlation was observed between them: Pearson's coefficient of 0.847 (P < 0.001) and 0.863 (P < 0.001), respectively. However, after stratifying by degrees of proteinuria, a poor correlation was found in the range of <500 mg/day and only 26.6% of 24-h P/C ratio was explained by the spot P/C ratio. Adding to this, for proteinuria range between 500 and 1000 mg/day, there was no correlation (Pearson's −0.098; P > 0.05). In fact, only 1% of 24-h measurements could be explained by the spot P/C ratio. CONCLUSIONS: Our study demonstrated a good correlation between 24-h proteinuria and random P/C ratio among patients with LN. However, this correlation was poor for proteinuria under 500 mg/day and did not exist in a range between 500 and 1000 mg/day. This finding is of greater importance because this range is quite common in patients with LN remission. Until further clarification, to the best of our knowledge, we maintain reluctant to completely substitute the 24-h collection by the P/C ratio especially when a renal flare is suspected, or before any change in therapy.